Navigating the Hospitality Horizon: Current Trends and Strategies for Customer Attraction and Retention in the Hotel Industry - Lilyana Bardukova (Икономика и компютърни науки, 2023)
The hospitality industry is undergoing rapid transformation, driven by technological innovations, shifting consumer preferences, and global events. This research explores the current trends and strategies employed by hotels to attract and retain customers in this dynamic landscape. In the realm of technological innovations, contactless check-in/check-out, mobile room keys and virtual reality experiences are reshaping the guest experience. Sustainability initiatives, encompassing green building practices, eco-friendly amenities, and community engagement, have become integral to hotel operations. Personalization and customization, driven by data-driven experiences, loyalty programs, and targeted marketing, play a pivotal role in enhancing guest satisfaction. Furthermore, health and safety measures, including enhanced cleaning protocols, health screenings, and wellness-focused services, are paramount in the post-pandemic era. The purpose of the present development is aimed at announcing the current trends and strategies for attracting and retaining customers in the hotel industry. The study uses qualitative analysis of hotel industry trends and case studies. The object of the study is geographically limited only to the hotel industry. Future studies should focus on expanding the sample for the restaurant industry as well as destinations. A set of research methods and approaches are used to achieve the goal and solve the tasks of the research, the most important of which are: theoretical analysis, comparative analysis. Results indicate a correlation between the adoption of technological innovations and positive hotel guest experiences. Sustainability initiatives contribute not only to environmental responsibility but also to positive brand perception. Personalization efforts, particularly through loyalty programs, show a direct impact on customer retention. The implementation of health and safety measures is crucial for rebuilding guest confidence and ensuring long-term sustainability. The discussion interprets these findings in the context of the broader hospitality landscape, addressing challenges, industry adaptation, and policy implications. Recommendations are provided for hotel practitioners, emphasizing the importance of aligning with emerging trends to stay competitive. The hotel industry can make actions to embrace innovation, adapt to changing consumer habits and foster a resilient and customer-centric approach in the ever-evolving hotel landscape.